A survey of pelvic types on computed tomography images - Vučinić, Nikola; Paulsen, Friedrich; Milinkov, Milan; Nikolić, Marijana Basta; Todorović, Snežana Tomašević; Knezi, Nikola; Nikolić, Uroš (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Background: In the medical literature several classifications of the pelvis according to its shape can be found. The most common classification distinguishes four general pelvis types: gynecoid, android, anthropoid and platypelloid. Natural childbirth may be significantly prolonged, difficult or even impossible if the pelvis shape is not in proportion to the size of the fetus. The objectives of our study were to calculate major diameters and conjugate diameters of the female bony pelvic ring and to determine the major pelvic types according to their shape. Based on the parameters obtained, we aimed to establish a relationship between some pelvic types and difficult childbirth. Methods: The study was prospective in design and included 54 female subjects of various ages who had been referred for computed tomography of the pelvis, as part of the diagnosis of an underlying condition. In each patient, five most important parameters in two planes were measured and the pelvic type was determined by using the brim index and a special formula for android type. All measurements were performed using the Vue PACS v 12.1.6.1005 program. The description of the pelvic inlet was used to confirm all pelvic types. Data on previous births were taken from the questionnaire filled out by the subjects during the radiological examination. Results: Gynecoid pelvic type was the most common in our sample (28 pelvises – 52%), followed by platypelloid type (11 pelvises – 20%), anthropoid type (8 pelvises – 15%) and finally android type (7 pelvises – 13%). There was a statistically significant difference in the diameter bispinous length (p < 0.05) between the platypelloid and anthropoid pelvic types. Pathological degree of stenosis was present in seven pelvises (the first degree in six pelvises and the second degree in one pelvis). The frequency of cesarean section was 31.82% and this technique was most frequently used in the subjects with a gynecoid pelvic type. The duration of natural labor ranged from 4 to 18 h. There was no statistically significant difference in the duration of labor between subjects with different pelvic types. Conclusions: Gynecoid pelvic type was present in more than half of our subjects. Although this type is considered ideal for labor, we have not established that it has a great influence on whether the labor will be performed naturally or by cesarean section, neither that it significantly affects the length of birth. The gross narrowing of the pelvic ring is present in non-gynecoid pelvic types. The data obtained will certainly be useful to the obstetrician when planning the labor and considering all the factors that may affect the course of birth.
CRIS-Team Scopus Importer:2022-04-29
Keywords: Computed tomography; Labor; Morphology; Pelvis; Types